LEARNING MOTIVATION OF RELIGIOUS PROGRAM IN SENIOR HIGH SCHOOL STUDENTS VIEWED FROM GENDER ANDIMPLICATION IN GUIDANCE AND COUNSELING - Yasrial Chandra; Rahmawati Wae (STIT Al-Ittihadiyah Labuhanbatu Utara, 2018)
Learning motivation can be defined as internal and external encouragement in the students to make a change over their behavior. Someone’s learning motivation is affected by various factors which might come either from themselves or from outside. One of the factors are gender. The purpose of this research was to reveal of religious program insenior high school students learning motivation viewed from gender and its implication in guidance and counseling. This research method was ex post facto. The population of this research was the students of religious program in senior high school that consist of 108 people. All of the population was taken as the sample. The instrument of the research was Likert scale model. The data obtained in this research was analyzed by using analysis of variant (ANOVA).The results of data analysis indicated thatlearning motivation of the male and female students were in high category in which the average scores of female students was higher than the male students. Keywords: Learning Motivation, Gende